2007
DOI: 10.3892/ijo.30.5.1205
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the prognostic value of loss of heterozygosity at the retinoblastoma gene in osteosarcoma

Abstract: The retinoblastoma (RB) tumour suppressor gene is implicated in the development of several malignancies including osteosarcoma. Recent studies postulated its loss of heterozygosity (LOH) to be a poor prognostic factor at diagnosis of osteosarcoma (OS). It remains unclear whether LOH of the RB gene is suitable as a prognostic factor at diagnosis in patients with osteosarcoma. In this study we aimed to determine the early prognostic value of RB-LOH as well as the ability of denaturating high performance liquid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 37 publications
(50 reference statements)
5
16
0
2
Order By: Relevance
“…The observation that ectopic expression of constitutively active RB resulted in transcriptional repression of E2F targets and other genes associated with cell cycle control and DNA replication is consistent with previously defined mechanisms (15). However, assessments of individual components of the RB pathway have not always correlated with event free or overall survival (37,38). Loss of heterozygosity of RB has been proposed as an indicator of poor prognosis in human osteosarcoma patients (39), but our work is the first .…”
Section: Functions Annotationsupporting
confidence: 86%
“…The observation that ectopic expression of constitutively active RB resulted in transcriptional repression of E2F targets and other genes associated with cell cycle control and DNA replication is consistent with previously defined mechanisms (15). However, assessments of individual components of the RB pathway have not always correlated with event free or overall survival (37,38). Loss of heterozygosity of RB has been proposed as an indicator of poor prognosis in human osteosarcoma patients (39), but our work is the first .…”
Section: Functions Annotationsupporting
confidence: 86%
“…The RB1-LOH rate of 43% in our study was comparable with the rate of 37.2% to 39% published in the literature (19,20). Allelic imbalances of the RB1 locus have previously been reported in osteosarcoma, but their predictive impact remains controversial.…”
Section: Loh Patterns In Osteosarcomasupporting
confidence: 75%
“…Earlier studies revealed high LOH rates for osteosarcoma at the 13q14 locus, and the authors found them to be associated with a poor prognosis (20,21). More recently, Heinsohn et al were not able to confirm this prognostic impact, which is in accordance with our findings (19). Remarkably, the LOH region on chromosome 10q21.1, harboring PCDH15 and ZWINT1, was more important in respect of prognostic discrimination (Fig.…”
Section: Loh Patterns In Osteosarcomasupporting
confidence: 61%
“…MSI is considered as a dysfunction of the mismatch repair (MMR) genes [5, 10 -12, 14], whereas LOH seems to correspond to genetic defects of tumour suppressor genes [7,16,21,22,24,26,27].…”
Section: Discussionmentioning
confidence: 99%